OPTIMASI KINERJA PELABUHAN PENYEBERANGAN KETAPANG – GILIMANUK - Suparsa, I Gusti Putu (Jurnal Ilmiah Teknik Sipil; Vol. 13, No. 1 Januari 2009, 2009)
The port of crossing between Ketapang and Gilimanuk connecting of Java and Bali Island represents very busy port after port of crossing between Merak and Bakauheni connecting of Java and Sumatra Island. Natural demand increases rapidly by years whereas facilities (number of berth) and basic facilities (number of ferries) are unable to balance it. This research was conducted in September 2008 at condition of normal operation by taking location at port of Ketapang. The objective of this research is to optimize in the event of problem or damage at one part of the system. Collected data cover growth of demand, condition of facilities, dock headway and also schedule which have been specified by PT. ASDP. Method used is single line analysis. The result shows by using technique of optimization when operation problem would possibly happen, the system still can give optimal service so that queue (lay time) passenger can be minimized.
Keywords: optimization, dock headway, ferries, cycle time.